Removal of Cyanotoxins in Detroit River Water Using Ozone-Based Advanced Oxidation Processes. (2nd September 2020) - Jasim, S.Y.; Uslu, M.; Seth, R.; Biswas, N.
ABSTRACT: The removal of cyanotoxins, microcystin-LR (MLR), anatoxin-a (ANA), and cylindrospermopsin (CYN) in Detroit River water (DRW) was investigated by ozone and advanced oxidation process (AOP). Enhanced removal of all cyanotoxins was observed with increasing applied ozone dose. The reactivity of cyanotoxins with ozone followed the order of MLR>CYN>ANA in DRW at its natural pH of 7.6, as indicated by the calculated pseudo first-order oxidation coefficients (kd ) of 17.5, 7.41, and 2.03 L/mg, respectively. The most efficient oxidations of MLR, CYN, and ANA with ozone in DRW were obtained at pH 5, 7.6, and 10, respectively, with kd values of 29.5, 7.41, and 4.65 L/mg. Ozone-based AOP with hydrogen peroxide did not make a significant difference in the removal of cyanotoxins compared to the application of ozone alone.